2016
DOI: 10.1002/jocb.135
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of the Relationship between Shared Leadership and Creativity in Inter‐Organizational Teams

Abstract: An inter‐organizational team, which consists of diverse members from different organizations to conduct an initiative, has been widely treated as a critical method to improve organizational innovation. This study proposes a multilevel model to test the relationship between shared leadership and creativity at both team‐ and individual level in the context of inter‐organizational teams. Multisource data were collected from 53 inter‐organizational teams. We obtain the following findings: first, shared leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 89 publications
2
73
0
Order By: Relevance
“…Shared leadership is conductive to knowledge sharing among team members, which will extend the team knowledge pool and provide cognitive resources for team creativity (Gong et al, ; Gu et al, ). In addition, scholars have found that shared leadership can promote team learning, which encourages team members to continuously learn new information, knowledge, and skills from each other to accomplish their own tasks (Liu, Hu, Li, Wang, & Lin, ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Shared leadership is conductive to knowledge sharing among team members, which will extend the team knowledge pool and provide cognitive resources for team creativity (Gong et al, ; Gu et al, ). In addition, scholars have found that shared leadership can promote team learning, which encourages team members to continuously learn new information, knowledge, and skills from each other to accomplish their own tasks (Liu, Hu, Li, Wang, & Lin, ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Shared leadership is conductive to knowledge sharing among team members, which will extend the team knowledge pool and provide cognitive resources for team creativity (Gong et al, 2013;Gu et al, 2018).…”
Section: The Mediating Effect Of Shared Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the content and evolution characteristics of interorganizational learning, the evolution content of interorganizational learning is the process of clarification, sharing, and internalization of relevant knowledge into another organization based on the perspective of system view. From different perspectives, scholars put forward many factors that affect the effectiveness of inter-organizational learning [40][41][42][43][44]. Zhu et al [40] proposed that there are four main factors affecting the effectiveness of interorganizational learning, namely, culture, structure, technology, and absorptive capacity.…”
Section: Criteria Framework For the Evaluation Of Enterprise Learningmentioning
confidence: 99%
“…Yayavaram et al [42] thought that the key elements of organizational learning are interaction between partners, high learning goals, trust, and long-term goal orientation. The degrees of trust between organizations, learning intention, partner's knowledge attribute, and organizational learning ability have great influence on knowledge transfer and interorganizational learning [43]. In order to realize the learning opportunities provided by the alliance, collaborators must attach importance to learning and consciously think about how to learn.…”
Section: Criteria Framework For the Evaluation Of Enterprise Learningmentioning
confidence: 99%